In Vitro Acylation of Okadaic Acid in the Presence of Various Bivalves’ Extracts - Keiichi Konoki; Tatsuya Onoda; Ryuichi Watanabe; Yuko Cho; Shinnosuke Kaga; Toshiyuki Suzuki; Mari Yotsu-Yamashita (Marine Drugs, 2013)
The dinoflagellate Dinophysis spp. is responsible for diarrhetic shellfish poisoning (DSP). In the bivalves exposed to the toxic bloom of the dinoflagellate, dinophysistoxin 3 (DTX3), the 7-OH acylated form of either okadaic acid (OA) or DTX1, is produced. We demonstrated in vitro acylation of OA with palmitoyl CoA in the presence of protein extract from the digestive gland, but not other tissues of the bivalve Mizuhopecten yessoensis. The yield of 7-O-palmitoyl OA reached its maximum within 2 h, was the highest at 37 °C followed by 28 °C, 16 °C and 4 °C and was the highest at pH 8 in comparison with the yields at pH 6 and pH 4. The transformation also proceeded when the protein extract was prepared from the bivalves Corbicula japonica and Crassostrea gigas. The OA binding protein OABP2 identified in the sponge Halichondria okadai was not detected in the bivalve M. yessoensis, the bivalve Mytilus galloprovincialis and the ascidian Halocynthia roretzi, though they are known to accumulate diarrhetic shellfish poisoning toxins. Since DTX3 does not bind to protein phosphatases 1 and 2A, the physiological target for OA and DTXs in mammalian cells, the acylation of DSP toxins would be related to a detoxification mechanism for the bivalve species.